Method for locating weak zones at coal-bedhost rock interface in the context of outburst hazard: Theory and laboratory experiment - Larisa Nazarova; Leonid Nazarov (Fracture and Structural Integrity)
Within the framework of a geomechanical model that describes deformation of rock mass during extraction of subhorizontal coal beds, the outburst hazard mechanism is substantiated: the approach of a working face to a weak zone at the coal-bedhost rock interface initiates tensile stress areas, which creates the prerequisites for the face spalling and loss of coal with methane. The inverse problem of determining conditions at the horizontal boundaries of a coal bed is formulated and solved using tomography data (patterns of P-wave velocity V) and the empirical dependence of V on the mean normal stress s. Lab-scale test results on stepwise compression of parallelepipeds made of artificial geomaterials are presented. Tomography of the specimens was performed by acoustic sounding data, and the pattern of velocities V* was obtained. Using the pre-found empirical dependence V(s) for geomaterial, the distribution s*=V-1(V*) in the specimen was calculated, which served as the input data for the inverse problem on the shear stresses sxy at the specimenpress plate interface. The inversion of the lab data confirmed the possibility of identifying weak zones at the boundaries where sxy0. These zones are associated with probable sources of failure and outbursts.